The Effect of Profitability, Leverage, and Firm Size on Firm Value in Non-Cyclical Consumer Sector Manufacturing Companies for 2021-2023 - Wishal Dafa Aushaf; Siti Nur Azizah; Amir Amir; Iwan Fakhruddin (Transpublika Publisher, 2025)
Company value represents a key benchmark in measuring financial performance and long-term viability for investors. This study investigates how profitability, leverage, and firm size influence company value in non-cyclical consumer sector manufacturing firms listed on the Indonesia Stock Exchange between 2021 and 2023. Through purposive sampling method, 183 firm-year observations were obtained and analyzed using multiple linear regression after all classical assumption tests were fulfilled. The research results show that profitability (β = –0.004; p < 0.001) and company size (β = –0.112; p < 0.001) have a significant negative effect on company value, while leverage (β = 0.509; p < 0.001) has a significant positive effect. The research model has strong explanatory power with an Adjusted R² of 0.904, meaning the three variables can explain 90.4% of the variation in company value. These findings confirm that in this sector, high profitability and large company scale do not always enhance investor perception, while optimal debt utilization can actually serve as a positive signal regarding the company's future prospects. This research expands understanding of Signaling Theory by showing that profitability and company size are not always perceived positively by investors, while leverage can serve as a signal of confidence in the company's prospects. Practically, these findings emphasize the importance of transparency, efficiency, and financial strategies that align with investor expectations in enhancing company value.